2006
DOI: 10.12942/lreg-2006-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and complying with EU governance outputs

Abstract: This essay takes stock of the literature on how European Union policies are being put into practice by the member states. It first provides an overview of the historical evolution of the field. After a relatively late start in the mid 1980s, the field has meanwhile developed into one of the growth industries within EU research. The paper identifies three different waves of EU implementation scholarship. The first wave considered implementation primarily a problem of institutional efficiency. In the second wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 32 publications
0
45
0
5
Order By: Relevance
“…While the limited literature on practical EU implementation has treated administrations as yet another source for non-compliance (Versluis 2007) or ignored the street-level of EU implementation (Treib 2014), this study has shown that lower level implementers are surprisingly aware of the multilevel legal context in which they operate. Most implementers eventually give priority to national guidance in their decisions (see also Mastenbroek 2017).…”
Section: Resultsmentioning
confidence: 80%
“…While the limited literature on practical EU implementation has treated administrations as yet another source for non-compliance (Versluis 2007) or ignored the street-level of EU implementation (Treib 2014), this study has shown that lower level implementers are surprisingly aware of the multilevel legal context in which they operate. Most implementers eventually give priority to national guidance in their decisions (see also Mastenbroek 2017).…”
Section: Resultsmentioning
confidence: 80%
“…The study of transposition of EU directives in the national legislations of the member states has become part of a very extensive literature (Mastenbroek 2005;Toshkov et al 2010;Treib 2014). A long-standing weakness of this literature has been the predominance of transposition studies taking the adoption of (directives) into national legislation as a measure for compliance.…”
Section: A Framework For Understanding Domestic Policy Implementationmentioning
confidence: 99%
“…The literature on compliance with EU law comprises more than three generations of studies using different models and approaches to transposition and policy implementation in the EU (Mastenbroek 2005;Toshkov et al 2010;Treib 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We assess and explain implementation in selected national contexts (see below). We employ two main approaches focusing on the relationship between the EU and member-state levels to explain variation in implementation (Treib 2008;Di Lucia and Kronsell 2010). The first centres on the degree of 'fit' between EU requirements and national status quo.…”
mentioning
confidence: 99%
“…Domestic politics explains responses to EU policies by the state (or its government) and society, and the relationship between the state and society (Underdal and Hanf 2000;Treib 2008;Di Lucia and Kronsell 2010). New governments may bring in new priorities after EU policies have been negotiated and adopted.…”
mentioning
confidence: 99%